Further studies of cyclical transmission and antigenic variation of the ILDar 1 serodeme of Trypanosoma vivax - Gardiner, Peter R.; Thatthi, R.; Gathuo, H.; Nelson, R.; Moloo, S.K. (Cambridge University Press, 1986)
Antigenic variation in the ILDar 1 serodeme of the naturally rodent-infective stock of West AfricanTrypanosoma vivaxhas been investigated following cyclical transmission. The immunofluorescent and immune lysis tests were employed with a panel of 39 variant-specific mouse antisera. When antigenically homogeneous, or mixed, populations were transmitted by tsetse flies to goats, the first peak parasitaemias arising in the goats were antigenic mixtures (up to 9 major, and several minor variants being recognized in some cases) from which the ingested variant was absent. Although first peak parasitaemias in similarly infected goats showed some variants in common, there was no obvious relationship between the VAT profiles in different goats. When these populations were expanded in irradiated mice, VAT heterogeneity was maintained with a tendency towards the development of predominant variants in some, but not all, instances. Six additional variants, derived following the growth of bloodstream form ILDat 1·9 in 37°C culture, were also represented in goat and mouse populations. Two further variants, isolated after cyclical development of ILDat 1·9-derived trypanosomesin vitro, were not present in the early parasitaemias in goats and mice.